Meningkatan Produktivitas Budidaya Ikan Melalui Sistem Monitoring Kualitas Air Di Desa Tapen Berbasis IoT - Rahmawati, Rina Dian; Aisa, Aufia; Nashoih , Afif Kholisun; Al Ghazali, Dzikrul Hakim; Nuryani, Nuryani; Attamimi, Muhammad Hamdan; Fadila, Salma Nailul; Al-Mulky, Ilham Imanullah; Erisa, Nina; Wati, Ani Rohmah; Hidayatulloh, Muhammad Kris Yuan (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
Cultivation is an activity that is an important sector in the community's economy. One of the activities that is popular with the community is fish farming. To increase fish cultivation, a water quality monitoring system is needed which aims to monitor temperature, pH, oxygen levels, and anomia. To achieve an efficient water quality cultivation system, IoT-based technology is needed. The location of this KKN is located in Tapen village, Kudu sub-district, Jombang regency. The method used in this activity is a question-and-answer method conducted with fish farmers. This activity aims to produce a hydropure meter tool that can help fish farmers monitor water conditions more efficiently and detect changes in water quality quickly. The resulting tool was tested in catfish ponds chosen by fish farmers in Tapen Village and data was obtained, namely pond 1 tds meter 269, temperature 28.19°C, ec 0.072; pool 2 tds quality 430, ec 1.18, temperature 28.63°C; pool 3 tds quality 307, ec 0.83 and temperature 29.75°C. The results of the trials above that have been carried out, show that the water quality and temperature of the catfish pond are good for fish cultivation.